THE EFFECTS OF 1 %. SODIUM CHLORIDE ADDITION ON THE COMPACTION AND STRENGTH PROPERTIES OF LIME SOIL STABILIZATIO - Sofjan, Kurniadi
An experimental study aimed at elucidating the mechanisms by which one per cent of sodium chloride improves the stability of lime stabilized soils is described. The pro-gramme was designed to study the compaction and strength properties of lime-stabilized soils rather than to investigate the exact chemical formulation of the final products. Experimental results indicated that the addition of one per cent of sodium chloride increased the stability, in terms of unconfined compressive strength and maximum dry density of lime-treated soils. However, the Plasticity Index became higher which meant that the mixtures were more sensitive to swell/expansion. The lime-sodium chloride-soil mixtures produced higher strength than the lime-treated soils for the same cost of materials. This revealed that the use of sodium chloride as an additive in the lime-stablized soils was economically viable